ISI Cancellation Using Blind Equalizer Based on DBC Model for MIMO-RFID Reader Reception - S. Duangsuwan; S. Promwong (My University, 2015)
Considering a dyadic backscatter channel (DBC) model, the previous methods with zero forcing (ZF) and minimum mean squared error (MMSE) are not able to rapidly cancel inter-symbol interference (ISI) because of errors of post-preamble transmission in MIMO-RFID channel.In order to achieve the ISI cancellation, the proposed method is demonstrated to improve the convergence rate without postpreamble by using a constant modulus algorithm (CMA) in this paper.The CMA depends on the steepest descent algorithm function, which is based on the second order statistics (SOS) to estimate the channel characterization.We compare between the conventional method and the proposed method based on simulation and measured data.Furthermore, the multiple tag of post-processing is also considered under the assumption of the maximum likelihood detection.We can confirm that the proposed method is better than the conventional method with faster ISI cancelling and a lower bit error rate (BER) improving up to 12 tags.
Keywords: dBc; Adaptive equalizer; RFID technology advancements